PENGARUH CURRENT RATIO DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maharani Rona Makom; Mirasanti Wahyuni (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The mining sector is one of the pillars of national economic development and is one of the strategic industries that have an important role for Indonesia. Strong natural resource commodity prices and the return of investor interest in the mining industry have spurred the market value of mining companies. The purpose of this study was to test whether the current ratio and return on assets affect the development industry companies listed on the Indonesia Stock Exchange. The study used data from 10 mining companies from 2015 to 2020. The data used is secondary data derived from the company's financial statements as well as from literature. The results of this research test are simultaneous current ratio and return on asset has a positive influence on the stock price while partial testing of current ratio has no effect on stock prices and return on assets has an effect on the stock price of mining companies on the Indonesia Stock Exchange (IDX)